The first outline of the fully-formed doctrine (Louvain, April 1920) - Maréchal, Joseph; Surzyn, Jacek; Bańka, Aleksander R. (Folia Philosophica, 2009)
The article contains a Polish translation of Joseph Maréchal's text: First outline of a fully formed doctrine (Louvain, April 1920).